Analysis of a self-help book translation for adolescent girls: Discursive tones, discursive ethos and female geek teenage identity - Furlan, Marília Molina [UNESP]; Amorim, Lauro Maia [UNESP] (My University, 2018)
This article proposes an analysis of the translation activity by considering the concept of tone and discursive ethos and the meaning effects derived from the female geek teenage identity in self-help bestsellers for adolescents. The theoretical framework was provided by the following: Mittmann (1999) on translation; Silva (2012) on the concept of identity, and Maingueneau (2008) on tone and discursive ethos. The analysis revealed that the images of the enunciators and of the female geek teenagers in the source text are characterized by humor, exaggeration, enthusiasm, pride, militancy and aggressiveness. However, two new aspects regarding ethos and the female geek teenage identity were discursively constructed in the translated text: moderation and reduction of colloquialism. These aspects were observed in the attenuation of the discursive tones originally adopted by the enunciator in the source text in English.
Análise da tradução de obra de autoajuda para garotas adolescentes: Tons do discurso, ethos discursivo e identidade geek feminina adolescente
Keywords: Enunciator; Image; Nerd; Tonality; Young